The Role of Fermi Resonance in Formation of Valence Band of Water Raman Scattering - Burikov, Sergey A.; Dolenko, Tatiana A.; Fadeev, Victor V. (Research Letters in Optics, 2008)
The role of Fermi resonance in formation of valence band of water Raman scattering was investigated. Simultaneous measurement of characteristics of bending and valence bands of water in D2O solutions, KBr, and KCl and using genetic algorithms in conjunction with variation methods allowed increasing accuracy of estimation of Fermi resonance coupling constant and of Fermi resonance contribution into formation of water Raman valence band.